ChatGPT: Empowering Self-Directed Writing Through Mind Mapping and Ai-Assisted Composition - Lasma Dwina (Future Science, 2024)
Since the beginning of 2020, the pandemic has prompted senior high school students to embark on a self-directed learning journey, adapting to the demands of remote education. In contrast to traditional learning environments, where teachers use an autocratic manner in the classroom, learners play an autonomous role in self-directed learning. This condition has revealed serious problems with English writing skills. This research described the process of mind mapping and ChatGPT for self-directed writing for senior high school students. The method of analyzing data in this research is by using three steps of qualitative analysis including data reduction, data display, and conclusion. Based on the research design, the researcher conducted the research by employing preliminary research and data collection followed by identifying recurring themes in observation, depth-in interviews, and survey responses. The researcher categorized themes related to self-monitoring, self-management, and motivational variables. Finally, it was followed by interpretation data It revealed that when properly taught, mind mapping provided a visual framework that motivated students to combine concepts and recognize connections. Combining these technologies may enable students to improve their compositions' coherence and writing skill quality. The combination of pedagogical techniques with AI technology has the potential to improve students' capacity for independent thought organization and effective communication, which is in line with the objectives of the changing educational landscape.